Transvaginal mesh-reconstruction of anterior apical prolapse: a selective implant choosing approach - O. V. Snurnitsyna; A. N. Nikitin; M. V. Lobanov; Zh. Sh. Inoyatov; L. M. Rapoport; M. E. Enikeev (Вестник урологии, 2022)
Introduction. Transvaginal mesh-reconstruction of urogenital prolapse remains a controversial trend in modern urogynecology. We have seen growth in transvaginal mesh surgery since 2004, followed by a sharp decline after 2011 due to FDA restrictions related to imperfections in previously available prostheses and implantation techniques. Improving the efficacy and minimizing complications of transvaginal mesh-surgery is at the forefront of research in the field of modern urogynecology.Purpose of the study. To optimize the indications for transvaginal mesh-reconstruction of anterior apical prolapse.Materials and methods. The study enrolled 375 patients with anterior apical prolapse. The grade of prolapse was assessed using POP-Q. In patients with endopelvic pelvic fascia insufficiency, severe cystocele (Aa ≥ +1) and hysteroptosis grade II – IV, the correction was carried out using the six-arm OPUR® («ABISS», Saint-Étienne, France). lightweight polypropylene monofilament implant (n = 290). When the cystocele was not prominent (Aa ≤ -1) and grade III – IV hysteroptosis, posterior sacrospinal hysteropexy was preferred with the CYRENE® («ABISS», Saint-Étienne, France) tape (n = 85). In 35 patients, the operation was combined with anterior colporrhaphy. In 5 patients, a simultaneous conization/amputation of the cervix was performed. The examination was performed 1 month after surgery and then annually. Prolapse ≥ grade II was as recurrent. The follow-up period of 67 patients was more than 4 years.Results. After OPUR® prosthesis implantation, recurrent hysteroptosis was detected in 6 women with cervical hypertrophy / elongation within a period of 1 mo to 3.5 yr and cystocele in 4 patients. The efficacy was 96%. In 9 patients, an postoperative ischuria was found associated with extensive dissection and hypotension of the bladder wall due to chronic urinary retention in severe cystocele. Urination improved in 88% of cases. In the remaining cases, long-term mediator and hormone replacement therapy were continued., One recurrent hysteroptosis was observed during the implantation of the CYRENE® prosthesis. No damage to the bladder was observed. Acute urinary retention was detected in 1 case, which resolved after intermittent catheterization. Conclusion. The availability of 2 types of transvaginal prostheses for various degrees and configurations of urogenital prolapses allows a differentiated approach to their choice. Both prostheses suggest reliable «reconstruction-imitation» of the sacroiliac ligament by sacrospinal hysteropexy. If necessary, the operation can be supplemented with anterior colporrhaphy. The prevalence of anterior prolapse with endopelvic fascia insufficiency requires more extensive reconstruction, which can be performed relatively safely and effectively by implantation of a 6-arm OPUR® prosthesis.